Electrochemical Activation of Graphite Nanosheets Decorated with Palladium Nanoparticles for High Performance Amperometric Hydrazine Sensor. Issue 4 (13th November 2015) - Karuppiah, Chelladurai; Velmurugan, Murugan; Chen, Shen‐Ming; Devasenathipathy, Rajkumar; Karthik, Raj; Wang, Sea‐Fue
Abstract: Herein, we have demonstrated a preparation of palladium nanoparticles on electroactivated graphite nanosheets modified screen printed carbon electrode (PdNPs‐EGNS/SPCE) by a simple electrochemical method. The well‐prepared electrocatalyst was potentially applied to the high performance electrocatalytic oxidation of hydrazine in neutral medium. The PdNPs‐EGNS novel composite was characterized by scanning electron microscope (SEM) and the average diameter and thickness of PdNPs and EGNS were found to be ∼38 nm and 85 nm, respectively. The high performance electrocatalytic determination of hydrazine was performed by the amperometric i ‐t method. The fabricated sensor displayed irreversible electrocatalytic oxidation of hydrazine with diffusion‐controlled electrode process. The oxidation of hydrazine at PdNPs‐EGNS/SPCE showed wider linear range 0.05–1415 µM and high sensitivity 4.382 µA µM −1 cm −2 . The as‐prepared electrocatalyst achieved quick response towards hydrazine with a lower detection limit 4 nM. Abstract :